2004
DOI: 10.1177/0013916503261384
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Spatial Syntax of Cognitive Maps to the Spatial Syntax of the Environment

Abstract: This article investigates the effects of the spatial configuration of the local environment on residents'spatial cognitions of their built environment by exam ining the relationship between the spatial syntax of sketch maps and the spatial syntax of the environment. Hampstead Garden Suburb in London was investigated in detail. Structured interview surveys were carried out to elicit residents' sketch maps of their local area. Analysis of the spatial characteristics of the area and of the sketch maps using space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 11 publications
3
50
0
3
Order By: Relevance
“…Haq and Zimring (2003) showed that this spatial syntax influences wayfinding behavior. In a related approach, Kim and Penn (2004) reported that the way subjects drew sketch maps of their neighborhood reflected biases toward axial lines with high numbers of branch points; a similar conclusion was drawn by Kuipers and Stankiewicz (2003) in matching robotic behavior to human wayfinding behavior. Similarly, Peponis et al (1990) found that subjects made especially frequent use of spaces through which many locations were accessible, including at times when the target location was unknown.…”
supporting
confidence: 63%
“…Haq and Zimring (2003) showed that this spatial syntax influences wayfinding behavior. In a related approach, Kim and Penn (2004) reported that the way subjects drew sketch maps of their neighborhood reflected biases toward axial lines with high numbers of branch points; a similar conclusion was drawn by Kuipers and Stankiewicz (2003) in matching robotic behavior to human wayfinding behavior. Similarly, Peponis et al (1990) found that subjects made especially frequent use of spaces through which many locations were accessible, including at times when the target location was unknown.…”
supporting
confidence: 63%
“…For SS, then, the problem is to fi nd the logical and cognitive meanings of its basic elements, which include the convex space, the axial line, and the isovist. Although quite a few research studies involve the axial map of SS and navigation in large-scale space, direct evidence establishing the cognitive importance of axial lines is rare (e.g., Conroy Dalton et al, eds., 2007;Zimring & Conroy Dalton, eds., 2003;Kim & Penn, 2004;Penn, 2003). Typically, these studies use a correlational study design, and use good correlations to argue that SS measures provide access to underlying cognitive processes and representations without explaining individual mechanisms underlying any observable statistical patterns.…”
Section: Problem 5: Convex Maps Axial Maps and Isovists Were Not Exmentioning
confidence: 99%
“…Several studies have supported this hypothesis on real-world navigation via eye-tracking data. The cognitive behavior in an urban environment is also believed to be contributed to the mental representations and symbolic icons in the urban environment [42,43]. In a study conducted by Turner, the syntactic representation of numerous urban streets was simulated, and it was found that the users prefer continuous paths for walking [44].…”
Section: Potential Of Vr In Visualizing the Cognitive Behavior Of Urbmentioning
confidence: 99%